2022
DOI: 10.1038/s41531-022-00361-4
|View full text |Cite
|
Sign up to set email alerts
|

Harmol promotes α-synuclein degradation and improves motor impairment in Parkinson’s models via regulating autophagy-lysosome pathway

Abstract: The abnormal accumulation of α-synuclein (α-syn) is a crucial factor for the onset and pathogenesis of Parkinson’s disease (PD), and the autophagy-lysosome pathway (ALP) contributes to α-syn turnover. AMP-activated protein kinase (AMPK) and the mammalian target of rapamycin (mTOR) regulate autophagy by initiating the macroautophagy cascade and promoting lysosomal biogenesis via increased transcription factor EB (TFEB) activity. Hence, activation of AMPK-mTOR-TFEB axis-mediated autophagy might promote α-syn cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Inhibiting α-syn aggregation is an attractive target for combating α-syn-induced PD, and several groups have focused on the disaggregation of α-syn as a therapeutic mechanism [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], and these have been summarized and placed in ascending year of publication in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Inhibiting α-syn aggregation is an attractive target for combating α-syn-induced PD, and several groups have focused on the disaggregation of α-syn as a therapeutic mechanism [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], and these have been summarized and placed in ascending year of publication in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Harmol has been reported to be an autophagy activator in a variety of disease models. For instance, harmol can activate the autophagy process by triggering extracellular signal-regulated kinase 1/2 (ERK1/2) and AMP-activated protein kinase [ 3 , 48 ]. Previous studies have reported that the activation of ERK or AMPK pathways were important for the host fighting against HSV infection [ 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the accumulation of different forms of α-synuclein is crucial in in vitro autophagy research of PD ( Guzzo et al, 2022 ). In this line, either monitoring of α-synuclein accumulation ( Xu et al, 2022 ) or exposing the cells to α-synuclein (e.g., oligomeric α-synuclein) ( Wang X. et al, 2020 ) to induce a pathological state are approaches used in PD research. Protein expression analysis by Western blot is commonly used to measure different forms of α-synuclein such as monomeric ( Alvarez-Erviti et al, 2013 ; di Domenico et al, 2019 ; Sackmann et al, 2019 ; Zeng et al, 2019 ; Sala et al, 2021 ; Mavroeidi et al, 2022 ), oligomeric ( Sala et al, 2021 ), and phosphorylated α-synuclein ( Xu et al, 2022 ).…”
Section: Parkinson’s Disease (Pd)mentioning
confidence: 99%
“…In this line, either monitoring of α-synuclein accumulation ( Xu et al, 2022 ) or exposing the cells to α-synuclein (e.g., oligomeric α-synuclein) ( Wang X. et al, 2020 ) to induce a pathological state are approaches used in PD research. Protein expression analysis by Western blot is commonly used to measure different forms of α-synuclein such as monomeric ( Alvarez-Erviti et al, 2013 ; di Domenico et al, 2019 ; Sackmann et al, 2019 ; Zeng et al, 2019 ; Sala et al, 2021 ; Mavroeidi et al, 2022 ), oligomeric ( Sala et al, 2021 ), and phosphorylated α-synuclein ( Xu et al, 2022 ). About 90% of the α-synuclein aggregates found in Lewy Bodies of brain tissue from PD patients are phosphorylated at serine 129 (Ser129-phosphorylated α-synuclein) ( Sasaki et al, 2015 ).…”
Section: Parkinson’s Disease (Pd)mentioning
confidence: 99%
See 1 more Smart Citation